Investigation of Job Satisfaction and Occupational Safety Perceptions of Employees in Wastewater Treatment Plants: Study of Istanbul - Uçan, Rüştü; Şanlıer, Hakan; Özay, Müge Ensari (International Journal of Occupational Safety and Health, 2020)
Background: There exist many fatal occupational accidents in the works carried out in wastewater treatment plants.Objective: This research was carried out to determine the relationship between job satisfaction levels and occupational safety perceptions of employees working in wastewater treatment plants.Methods: In this study, a questionnaire including Minnesota Job Satisfaction Scale and Occupational Safety Scale is applied to a total of 161 people aged 16-65 years working in two different Advanced Biological Wastewater Treatment Plants in Istanbul by simple random sampling. Statistical Package for Social Science version-22 was used. Seventeen hypotheses were analyzed to show the relation between the occupational safety perceptions and socio-demographic parameters of employees.Results: The results show that there is no significant relationship between job satisfaction and occupational safety perception of the personnel working in wastewater treatment plants (F=0.096 and p=0.227 >0.05). On the other hand, it is found that there is a statistically significant difference between the level of job satisfaction perception and age of the employees (F=2.358 and p=0.002